IMPLEMENTASI PARADIGMA BARU PENDIDIKAN AGAMA ISLAM DALAM PEMBELAJARAN FIKIH SEBAGAI ROADMAP PEMBARUAN PAI DI MA AZZAINIYYAH SUKABUMI - Kurniati Kurniati; Mulyawan Safwandy Nugraha (CV. Adiba Aisha Amira, 2026)
Islamic Religious Education (IRE), particularly Fiqh instruction, continues to face challenges related to normative–doctrinal approaches, limited contextualization, and insufficient responsiveness to social dynamics and technological developments. This study aims to describe the implementation of the new paradigm of Islamic Religious Education in Fiqh learning, analyze the instructional strategies and methods employed, and formulate a roadmap for IRE reform based on classroom practices at MA Azzainiyyah. A qualitative case study approach was employed. Data were collected through in-depth interviews with the vice principal for curriculum affairs, a Fiqh teacher, and students, as well as classroom observations and document analysis. Data were analyzed using descriptive qualitative techniques with source and method triangulation. The findings indicate that the new IRE paradigm has been implemented through the strengthening of moral and character education, contextual and participatory learning, the integration of digital technology, and the promotion of religious moderation. Based on these findings, a roadmap for IRE reform is proposed, emphasizing meaningful, moderate, and adaptive Fiqh learning in response to contemporary educational challenges.